An antistatic packaging composite film and a preparation process thereof
Patent Information
- Application Number
- CN202610978405.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-20
AI Technical Summary
[0015]本发明基于分子设计原理,以氨基羟基单体(5-氨基-1-戊醇、二甘醇胺或四甘醇胺)、1,3-丙磺酸内酯和油酰氯为原料,通过双开环反应和亲核取代反应,合成长链烯基化磺酸钠型防静电剂;
Smart Images

Figure SMS_7 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of antistatic packaging materials technology, specifically to an antistatic packaging composite film and its preparation process. Background Technology
[0002] As electronic components become increasingly miniaturized and integrated, integrated circuits, semiconductor devices, and precision electronic assemblies are highly susceptible to latent damage or functional failure due to electrostatic discharge (ESD) throughout their entire lifecycle, from production and transportation to storage. Antistatic packaging bags have become a crucial material for ensuring the reliability and safety of electronic components. Among these materials, PE film, due to its excellent moisture resistance, low cost, and mature supply chain, has become the mainstream material for manufacturing antistatic packaging bags, accounting for over 60% of the market.
[0003] However, pure PE film has low polarity, poor water absorption, and strong insulation properties (surface resistivity of 10). 16 -10 20 The PE film's inherent strength (Ω) is insufficient to meet antistatic requirements. Currently, adding antistatic agents to PE films is a crucial way to achieve their antistatic function. Traditional antistatic agents are typically amphiphilic surfactants with both hydrophobic and hydrophilic groups (such as alkyl quaternary ammonium salts and alkyl sulfonates). These antistatic agents have small molecules that easily migrate from the plastic interior to the surface, achieving an antistatic effect by adsorbing surface moisture. However, they also suffer from drawbacks such as easy loss and short-lasting antistatic effect. Furthermore, the inherent mechanical strength of pure PE film is low, making it unable to effectively resist physical damage such as external punctures or tears that may occur during transportation.
[0004] Based on this, the present invention aims to develop a high-strength PE film with long-lasting antistatic function for manufacturing antistatic packaging bags for electronic components. Summary of the Invention
[0005] This invention utilizes a self-developed long-chain alkenylated sodium sulfonate antistatic agent and long-chain alkenylated nylon 6 resin to modify polyethylene resin through a free radical grafting reaction, thereby obtaining a high-strength antistatic polyethylene masterbatch. Using this masterbatch as raw material, an antistatic packaging composite film product is produced through a three-layer co-extrusion blow molding process. This film product has excellent antistatic and mechanical properties and exhibits a long-lasting antistatic effect, and can be used to manufacture antistatic packaging bags for electronic components.
[0006] An antistatic packaging composite film is provided, wherein the composite film is obtained by co-extrusion blow molding of high-strength antistatic polyethylene masterbatch, and the high-strength antistatic polyethylene masterbatch is obtained by melt grafting reaction of the following components: 90-110 parts by weight of low-density polyethylene resin: 1-5 parts by weight of long-chain alkenylated sodium sulfonate type antistatic agent; 3-7 parts by weight of long-chain alkenylated nylon 6 resin; Among them, the long-chain alkenylated sodium sulfonate type antistatic agent is one of the following: long-chain alkenylated sodium sulfonate type antistatic agent I, long-chain alkenylated sodium sulfonate type antistatic agent II, and long-chain alkenylated sodium sulfonate type antistatic agent III. Long-chain alkenylated nylon 6 resin is prepared by amidation grafting reaction of the acyl chloride functional group of oleoyl chloride with the amino group at the end of the nylon 6 molecular chain.
[0007] Preferably, the preparation method of the long-chain alkenylated nylon 6 resin is as follows: based on nylon 6 with a terminal amino content of 40-50 mmol / kg, oleoyl chloride is used for solution grafting modification. Under the conditions of acyl chloride molar ratio to terminal amino group (1.3-1.7):1 and reaction at 85-95℃ for 4-6 h, the grafting rate of the obtained long-chain alkenylated nylon 6 resin is 0.8-1.2 wt%.
[0008] Preferably, the thickness of the antistatic packaging composite film is 95-105 μm.
[0009] A process for preparing an antistatic packaging composite film includes the following steps: Step 1: Preparation of long-chain alkenylated sodium sulfonate type antistatic agent; Step 2: Nylon 6 resin is modified by solution grafting using oleoyl chloride via an amidation condensation reaction of acyl chloride and amino groups to obtain long-chain alkenylated nylon 6 resin. Step 3: Blend low-density polyethylene resin matrix, long-chain alkenylated nylon 6 resin and long-chain alkenylated sodium sulfonate antistatic agent, add initiator, and carry out melt grafting reaction to obtain high-strength antistatic polyethylene masterbatch. Step 4: Using high-strength antistatic polyethylene masterbatch as raw material, an antistatic packaging composite film is produced through a three-layer co-extrusion blow molding process.
[0010] Preferably, the preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent I is as follows: Using 1 molar equivalent of 5-amino-1-pentanol and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in 5-amino-1-pentanol and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate I. Using 1 molar equivalent of sodium hydroxysulfonate I and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent I is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate I and the acyl chloride functional group of oleoyl chloride.
[0011] Preferably, the preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent II is as follows: Using 1 molar equivalent of diethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in diethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate II. Using 1 molar equivalent of sodium hydroxysulfonate II and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent II is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate II and the acyl chloride functional group of oleoyl chloride.
[0012] Preferably, the preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent III is as follows: Using 1 molar equivalent of tetraethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in tetraethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate III. Using 1 molar equivalent of sodium hydroxysulfonate III and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent III is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate III and the acyl chloride functional group of oleoyl chloride.
[0013] Preferably, the preparation method of the high-strength antistatic polyethylene masterbatch is as follows: Low-density polyethylene resin, long-chain alkenylated sodium sulfonate antistatic agent, and long-chain alkenylated nylon 6 resin are fed into a twin-screw extruder through the main feed port. An initiator is injected into the molten material stream through a side feed port. The free radicals generated by the decomposition of the initiator initiate a grafting reaction between the low-density polyethylene resin matrix and the octadecene groups in the long-chain alkenylated nylon 6 resin and the long-chain alkenylated sodium sulfonate antistatic agent. After extrusion and granulation, a high-strength antistatic polyethylene masterbatch is obtained.
[0014] Preferably, the initiator is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; Preferably, the amount of the initiator is 0.1-0.5 wt% of the amount of low-density polyethylene resin. Preferably, the process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-6 are 175-185℃, 185-195℃, 190-205℃, 200-210℃, 205-210℃, and 195-205℃, respectively. Beneficial effects
[0015] Based on the principle of molecular design, this invention uses aminohydroxy monomers (5-amino-1-pentanol, diethylene glycolamine or tetraethylene glycolamine), 1,3-propanesulfonic acid lactone and oleoyl chloride as raw materials to synthesize long-chain alkenylated sodium sulfonate antistatic agents through double ring-opening reaction and nucleophilic substitution reaction. Long-chain alkenylated nylon 6 resin was prepared by solution grafting modification of nylon 6 resin through an amidation condensation reaction of oleoyl chloride and acyl chloride-amino group. The low-density polyethylene resin matrix is grafted with the octadecyl group in the long-chain alkenylated nylon 6 resin and the long-chain alkenylated sodium sulfonate antistatic agent by the free radicals generated by the decomposition of the initiator. The low-density polyethylene resin, the long-chain alkenylated sodium sulfonate antistatic agent and the long-chain alkenylated nylon 6 resin are melt-blended and granulated by a twin-screw extruder to obtain a high-strength antistatic polyethylene masterbatch. Using high-strength antistatic polyethylene masterbatch as raw material, an antistatic packaging composite film product is produced through a three-layer co-extrusion blow molding process. The volume resistivity of this film product is <10 Ω·cm. 9 It has a strength of Ω·cm, good static dissipation capability, and longitudinal tensile strength >44MPa and puncture resistance >50N / mm, exhibiting excellent antistatic and mechanical properties. Detailed Implementation Example 1:
[0016] The preparation steps for long-chain alkenylated sodium sulfonate type antistatic agent I are as follows: Step 1: Using 1 molar equivalent of 5-amino-1-pentanol and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction occurs between the more reactive amino functional group of 5-amino-1-pentanol and 1,3-propanesulfonic acid lactone, followed by neutralization under the action of sodium carbonate, to produce sodium hydroxysulfonate I, whose chemical structural formula is: ; Step 2: Using 1 molar equivalent of sodium hydroxysulfonate I and 1 molar equivalent of oleoyl chloride as raw materials, a nucleophilic substitution reaction is carried out between the hydroxyl functional group of sodium hydroxysulfonate I and the acyl chloride functional group of oleoyl chloride to generate a long-chain alkenylated sodium sulfonate type antistatic agent I, the chemical structural formula of which is: ; The specific experimental steps for preparing long-chain alkenylated sodium sulfonate type antistatic agent I are as follows: 2.5 g of 1,3-propanesulfonic acid lactone (CAS No. 1120-71-4) was dissolved in 20 mL of anhydrous methanol to form a 1,3-propanesulfonic acid lactone solution. Under nitrogen protection, 1.0 g of 5-amino-1-pentanol (CAS No. 2508-29-4) and 10 mL of anhydrous methanol were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, the 1,3-propanesulfonic acid lactone solution was slowly added dropwise to the three-necked flask and stirred at room temperature for 30 min. The mixture was then heated to 65 °C and stirred for 30 h. After cooling to room temperature, 10 mL of 1.5 mol / L sodium carbonate aqueous solution was added dropwise and stirred at room temperature for 2 h. The mixture was filtered, and the residual solvent was removed by rotary evaporation. Recrystallization was performed using a methanol / acetone mixed solvent (methanol and acetone volume ratio of 3:2). The solution was dried under vacuum at 50 °C for 2 h to obtain sodium hydroxysulfonate I. Under nitrogen protection, 1.5 g of oleoyl chloride (CAS No. 112-77-6) and 20 mL of anhydrous tetrahydrofuran were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 20 mL of anhydrous tetrahydrofuran solution containing 2.0 g of sodium hydroxysulfonate I and 2.1 mL of triethylamine were added to the three-necked flask in sequence. The mixture was heated to 50 °C and stirred for 6 h. After cooling to room temperature, the solvent was removed by rotary evaporation. The mixture was washed with deionized water and dried under vacuum at 50 °C for 2 h to obtain long-chain alkenylated sodium sulfonate type antistatic agent I. The 1H NMR characterization of long-chain alkenylated sodium sulfonate type antistatic agent I is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.87-0.90 (t, 3H), 1.20-1.31 (m, 20H), 1.49-1.57 (m, 6H), 1.64-1.70 (m, 2H), 1.75-1 .85(m, 8H), 2.29-2.36(m, 4H), 2.51-2.54(t, 4H), 2.83-2.86(t, 4H), 4.07-4.10(t, 2H), 5.28-5.36(m, 2H). Example 2:
[0017] The preparation steps for long-chain alkenylated sodium sulfonate type antistatic agent II are as follows: Step 1: Using 1 molar equivalent of diethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction occurs between the more reactive amino functional group in diethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by neutralization under the action of sodium carbonate, to generate sodium hydroxysulfonate II, whose chemical structural formula is: ; Step 2: Using 1 molar equivalent of sodium hydroxysulfonate II and 1 molar equivalent of oleoyl chloride as raw materials, a nucleophilic substitution reaction is carried out between the hydroxyl functional group of sodium hydroxysulfonate II and the acyl chloride functional group of oleoyl chloride to generate a long-chain alkenylated sodium sulfonate type antistatic agent II, the chemical structural formula of which is: ; The specific experimental steps for preparing long-chain alkenylated sodium sulfonate type antistatic agent II are the same as those for preparing long-chain alkenylated sodium sulfonate type antistatic agent I. The only difference is that 1.0 g of diethylene glycolamine (CAS No. 929-06-6) is used instead of 1.0 g of 5-amino-1-pentanol; and 2.0 g of sodium hydroxysulfonate II is used instead of 2.0 g of sodium hydroxysulfonate I. The 1H NMR characterization of long-chain alkenylated sodium sulfonate type antistatic agent II is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.88-0.91 (t, 3H), 1.19-1.31 (m, 20H), 1.53-1.58 (m, 2H), 1.75-1.86 (m, 8H), 2.30-2.33 (t, 2H) ), 2.55-2.58(t, 4H), 2.84-2.87(t, 4H), 3.10-3.13(t, 2H), 3.59-3.64(m, 4H), 4.27-4.30(t, 2H), 5.28-5.35(m, 2H). Example 3:
[0018] The preparation steps for long-chain alkenylated sodium sulfonate type antistatic agent III are as follows: Step 1: Using 1 molar equivalent of tetraethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction occurs between the more reactive amino functional group in tetraethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by neutralization under the action of sodium carbonate, to generate sodium hydroxysulfonate III, whose chemical structural formula is: ; Step 2: Using 1 molar equivalent of sodium hydroxysulfonate III and 1 molar equivalent of oleoyl chloride as raw materials, a nucleophilic substitution reaction is carried out between the hydroxyl functional group of sodium hydroxysulfonate III and the acyl chloride functional group of oleoyl chloride to generate a long-chain alkenylated sodium sulfonate type antistatic agent III, the chemical structural formula of which is: ; The specific experimental steps for preparing long-chain alkenylated sodium sulfonate type antistatic agent III are the same as those for preparing long-chain alkenylated sodium sulfonate type antistatic agent I. The only difference is that 1.9g of tetraethylene glycolamine (CAS No. 86770-74-3) is used instead of 1.0g of 5-amino-1-pentanol; and 2.4g of sodium hydroxysulfonate III is used instead of 2.0g of sodium hydroxysulfonate I. The 1H NMR characterization of long-chain alkenylated sodium sulfonate type antistatic agent III is as follows: 1H NMR (CDCl3, 400MHz) δ: 0.88-0.92 (t, 3H), 1.20-1.32 (m, 20H), 1.51-1.56 (m, 2H), 1.74-1.88 (m, 8H), 2.29-2.31 (t, 2H) ), 2.56-2.59(t, 4H), 2.73-2.76(t, 2H), 2.86-2.89(t, 4H), 3.60-3.70(m, 12H), 4.31-4.33(t, 2H), 5.32-5.39(m, 2H). Example 4:
[0019] Preparation of long-chain alkenylated nylon 6 resin: Based on the amidation condensation reaction of acyl chloride and amino group, nylon 6 resin (type F136, terminal amino content of 40.9 mmol / kg) was modified by solution grafting with oleoyl chloride. Under the conditions of acyl chloride molar ratio of 1.5:1 to terminal amino group and reaction at 90℃ for 5 h, after purification and drying, the actual grafting rate of long-chain alkenylated nylon 6 resin was determined by terminal amino titration method. The specific experimental steps for preparing long-chain alkenylated nylon are as follows: 100 parts by weight of nylon 6 resin and 1000 parts by weight of anhydrous N,N-dimethylformamide were added to a three-necked flask, heated to 80°C and stirred for 2 hours to dissolve. After cooling to room temperature, under nitrogen protection, 20 parts by weight of anhydrous N,N-dimethylformamide solution containing 1.8 parts by weight of oleoyl chloride was added to the three-necked flask. The mixture was heated to 90°C and stirred for 5 hours. After the reaction was completed, the reaction solution was poured into 10 times its volume of vigorously stirred deionized water to precipitate. The precipitate was filtered, the solid was collected, and the free oleoyl chloride was removed by Soxhlet extraction with acetone for 24 hours. The solid was then dried under vacuum at 70°C for 6 hours to obtain long-chain alkenylated nylon 6 resin. Example 5:
[0020] The high-strength antistatic polyethylene masterbatch I was prepared with the following formula: 100 parts by weight of low-density polyethylene resin (model LD 150DW), 2 parts by weight of long-chain alkenylated sodium sulfonate antistatic agent I, and 5 parts by weight of long-chain alkenylated nylon 6 resin. The preparation method is as follows. Low-density polyethylene resin, long-chain alkenylated sodium sulfonate antistatic agent I, and long-chain alkenylated nylon 6 resin are fed into a twin-screw extruder through the main feed port and melted at 180-205℃. A metered initiator, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, is injected into the molten material stream through the side feed port. The free radicals generated by the decomposition of the initiator initiate a grafting reaction between the low-density polyethylene resin matrix and the octadecene groups in the long-chain alkenylated nylon 6 resin and the long-chain alkenylated sodium sulfonate antistatic agent I. After extrusion and granulation, high-strength antistatic polyethylene masterbatch I is obtained. The specific experimental steps for preparing high-strength antistatic polyethylene masterbatch I are as follows: 100 parts by weight of low-density polyethylene resin, 2 parts by weight of long-chain alkenylated sodium sulfonate antistatic agent I, and 5 parts by weight of long-chain alkenylated nylon 6 resin were added to a twin-screw extruder through the main feed port to melt. Then, 0.2 g of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane was injected into the molten material stream through the side feed port. The mixture was then extruded and granulated to obtain high-strength antistatic polyethylene masterbatch I. The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-6 are 180℃, 190℃, 200℃, 205℃, 205℃, and 200℃, respectively, and the rotation speed is 200r / min. Example 6:
[0021] High-strength antistatic polyethylene masterbatch II was prepared. The only difference between it and high-strength antistatic polyethylene masterbatch I is that long-chain alkenylated sodium sulfonate type antistatic agent I was replaced with long-chain alkenylated sodium sulfonate type antistatic agent II. Example 7:
[0022] High-strength antistatic polyethylene masterbatch III was prepared, and its only difference from high-strength antistatic polyethylene masterbatch I was that long-chain alkenylated sodium sulfonate type antistatic agent I was replaced with long-chain alkenylated sodium sulfonate type antistatic agent III. Example 8:
[0023] The preparation of an antistatic packaging composite film includes the following steps: Step 1: Set the antistatic packaging composite film to a three-layer film structure, with each layer containing 100wt% high-strength antistatic polyethylene masterbatch in a mass ratio of 40:20:40. Step 2: The raw materials for each film layer are fed into the hoppers of the three screw extruders of the three-layer co-extrusion film blow molding unit. The molten resin is combined at the die head through the distributor, and then extruded and blown through the die head (the blow-up ratio is controlled at 2.9). After cooling and winding, an antistatic packaging composite film is obtained. The process parameters of the screw extruder corresponding to each film layer are set as follows: the temperatures of zones 1-3 are 180℃, 195℃, and 205℃, respectively; the flow channel temperature is 200℃; and the rotation speed is 50r / min. Among them, the high-strength antistatic polyethylene masterbatch is one of the high-strength antistatic polyethylene masterbatches I, II, and III; When the high-strength antistatic polyethylene masterbatches are respectively high-strength antistatic polyethylene masterbatches I, II, and III, antistatic packaging composite films I, II, and III are prepared in sequence. Comparative Example 1:
[0024] The preparation method of PE film a differs from that of antistatic packaging composite film I only in that low-density polyethylene resin (model LD 150DW) is used instead of high-strength antistatic polyethylene masterbatch I. Comparative Example 2:
[0025] The preparation method of PE film b differs from that of antistatic packaging composite film I only in that: high-strength antistatic polyethylene masterbatch I is replaced with blended antistatic polyethylene masterbatch. The preparation method of blended antistatic polyethylene masterbatch is as follows: 100 parts by weight of low-density polyethylene resin and 2 parts by weight of conventional sodium sulfonate antistatic agent (sodium octadecyl sulfonate: CAS No. 13893-34-0) are added to a twin-screw extruder for melt blending, extrusion granulation, and blended to obtain blended antistatic polyethylene masterbatch. The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-6 are 160℃, 170℃, 180℃, 185℃, 185℃, and 180℃, respectively, and the rotation speed is 200r / min. Performance testing:
[0026] I. Thickness Test: The thickness of the film sample was tested using a thickness gauge in accordance with GB / T 6672-2001 "Mechanical Measurement Method for Determination of Thickness of Plastic Films and Sheets". II. Appearance Test: The appearance of the membrane sample is judged by visual inspection; III. Antistatic Performance Test: The volume resistivity of the film sample was measured according to GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity". Before the test, the sample was kept in a stable state for 24 hours under normal standard environmental conditions (25℃, 50%RH). The sample size was 100mm×100mm and the test voltage was 200V. IV. Long-term antistatic performance test: (1) First, place the membrane sample under normal standard environmental conditions (25℃, 50%RH) for 90 days (simulating the product storage process). Then, measure the volume resistivity of the membrane sample according to GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity". The sample size is 100mm×100mm and the test voltage is 200V. Calculate the change rate of volume resistivity of the sample after 90 days under standard conditions. (2) First, the membrane sample was subjected to a friction test using a reciprocating friction tester (simulating the friction during product transportation and packaging). The friction pressure was 0.5 kPa, the friction method was the same material membrane sample rubbing against each other, and the number of friction cycles was 1000. Then, the sample was placed under conventional standard environmental conditions (25℃, 50%RH) for 24 hours to stabilize the sample state. Finally, the volume resistivity of the membrane sample was measured according to GB / T 31838.2-2019 "Dielectric and resistive properties of solid insulating materials - Part 2: Resistive properties (DC method) - Volume resistivity and volume resistivity". The sample size was 100 mm × 100 mm and the test voltage was 200 V. V. Mechanical property testing: (1) Tensile strength test: The longitudinal tensile strength of the film sample was measured in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets" (the blowing direction is longitudinal). The sample size was 150mm × 20mm (sampled along the blowing direction) and the stretching rate was 100mm / min. (2) Puncture resistance test: According to GB / T 37841-2019 "Test method for puncture resistance of plastic films and sheets", a 5cm×5cm film sample was fixed on the puncture resistance tester. The puncture needle was made of stainless steel with a diameter of 1.0mm and a hemispherical tip with a radius of 0.5mm. The puncture rate was 50mm / min. The puncture resistance of the sample was recorded. The results of the above performance experiments are shown in Table 1.
[0027] Table 1. Performance test results of antistatic packaging composite film
[0028] A comprehensive analysis of the above experimental results leads to the following conclusions: Conclusion 1: Referring to national industry standards and enterprise user requirements: when 10 6 Ω·cm≤volume resistivity≤10 9 When the value is Ω·cm, the material is considered to have good electrostatic dissipation capability; Accordingly, the antistatic packaging composite film product prepared by the present invention exhibits excellent antistatic performance and has a long-lasting antistatic effect. Among them, the antistatic packaging composite film Ⅲ prepared by long-chain alkenyl sodium sulfonate antistatic agent Ⅲ has the lowest volume resistivity and the best antistatic performance. This is because the long-chain alkenyl sodium sulfonate antistatic agent Ⅲ contains a more flexible long ether chain. When its hydrophobic end is anchored to the polyethylene molecular chain through chemical bonds, the flexibility of the long ether chain gives the hydrophilic end of sodium sulfonate a higher degree of freedom, making it easier to orient and accumulate on the film surface, forming an effective hydrophilic conductive layer, thereby playing an antistatic function. Conclusion 2: The antistatic packaging composite film product prepared by the present invention using independently developed high-strength antistatic polyethylene masterbatch has achieved a significant improvement in mechanical properties compared with PE film prepared using conventional low-density polyethylene resin.
Claims
1. An antistatic packaging composite film, characterized in that, The composite film is obtained by co-extrusion blow molding of high-strength antistatic polyethylene masterbatch, which is obtained by melt grafting reaction of the following components: 90-110 parts by weight of low-density polyethylene resin: 1-5 parts by weight of long-chain alkenylated sodium sulfonate type antistatic agent; 3-7 parts by weight of long-chain alkenylated nylon 6 resin; Among them, the long-chain alkenylated sodium sulfonate type antistatic agent is one of the following: long-chain alkenylated sodium sulfonate type antistatic agent I, long-chain alkenylated sodium sulfonate type antistatic agent II, and long-chain alkenylated sodium sulfonate type antistatic agent III. The chemical structural formula of long-chain alkenylated sodium sulfonate type antistatic agent I is: ; The chemical structural formula of long-chain alkenylated sodium sulfonate type antistatic agent II is: ; The chemical structural formula of long-chain alkenylated sodium sulfonate type antistatic agent III is: ; Long-chain alkenylated nylon 6 resin is prepared by amidation grafting reaction of the acyl chloride functional group of oleoyl chloride with the amino group at the end of the nylon 6 molecular chain.
2. The antistatic packaging composite film according to claim 1, characterized in that, The preparation method of the long-chain alkenylated nylon 6 resin is as follows: based on nylon 6 with a terminal amino content of 40-50 mmol / kg, oleoyl chloride is used for solution grafting modification. Under the conditions of molar ratio of acyl chloride group to terminal amino group (1.3-1.7):1 and reaction at 85-95℃ for 4-6 h, the grafting rate of the obtained long-chain alkenylated nylon 6 resin is 0.8-1.2 wt%.
3. The antistatic packaging composite film according to claim 1, characterized in that, The thickness of the antistatic packaging composite film is 95-105μm.
4. The preparation process of an antistatic packaging composite film according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Preparation of long-chain alkenylated sodium sulfonate type antistatic agent; Step 2: Nylon 6 resin is modified by solution grafting using oleoyl chloride via an amidation condensation reaction of acyl chloride and amino groups to obtain long-chain alkenylated nylon 6 resin. Step 3: Blend low-density polyethylene resin matrix, long-chain alkenylated nylon 6 resin and long-chain alkenylated sodium sulfonate antistatic agent, add initiator, and carry out melt grafting reaction to obtain high-strength antistatic polyethylene masterbatch. Step 4: Using high-strength antistatic polyethylene masterbatch as raw material, an antistatic packaging composite film is produced through a three-layer co-extrusion blow molding process.
5. The preparation process of an antistatic packaging composite film according to claim 4, characterized in that, The preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent I is as follows: Using 1 molar equivalent of 5-amino-1-pentanol and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in 5-amino-1-pentanol and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate I. Using 1 molar equivalent of sodium hydroxysulfonate I and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent I is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate I and the acyl chloride functional group of oleoyl chloride.
6. The preparation process of an antistatic packaging composite film according to claim 4, characterized in that, The preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent II is as follows: Using 1 molar equivalent of diethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in diethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate II. Using 1 molar equivalent of sodium hydroxysulfonate II and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent II is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate II and the acyl chloride functional group of oleoyl chloride.
7. The preparation process of an antistatic packaging composite film according to claim 4, characterized in that, The preparation method of the long-chain alkenylated sodium sulfonate type antistatic agent III is as follows: Using 1 molar equivalent of tetraethylene glycolamine and 2 molar equivalents of 1,3-propanesulfonic acid lactone as raw materials, a double ring-opening reaction is carried out between the more active amino functional group in tetraethylene glycolamine and 1,3-propanesulfonic acid lactone, followed by a neutralization reaction under the action of sodium carbonate, to generate sodium hydroxysulfonate III. Using 1 molar equivalent of sodium hydroxysulfonate III and 1 molar equivalent of oleoyl chloride as raw materials, a long-chain alkenylated sodium sulfonate type antistatic agent III is generated by a nucleophilic substitution reaction between the hydroxyl functional group of sodium hydroxysulfonate III and the acyl chloride functional group of oleoyl chloride.
8. The preparation process of an antistatic packaging composite film according to claim 4, characterized in that, The preparation method of the high-strength antistatic polyethylene masterbatch is as follows: Low-density polyethylene resin, long-chain alkenylated sodium sulfonate antistatic agent, and long-chain alkenylated nylon 6 resin are fed into a twin-screw extruder through the main feed port. An initiator is injected into the molten material stream through a side feed port. The free radicals generated by the decomposition of the initiator initiate a grafting reaction between the low-density polyethylene resin matrix and the octadecene groups in the long-chain alkenylated nylon 6 resin and the long-chain alkenylated sodium sulfonate antistatic agent. After extrusion and granulation, a high-strength antistatic polyethylene masterbatch is obtained.
9. The preparation process of an antistatic packaging composite film according to claim 8, characterized in that, The initiator is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; The amount of the initiator is 0.1-0.5 wt% of the amount of low-density polyethylene resin. The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-6 are 175-185℃, 185-195℃, 190-205℃, 200-210℃, 205-210℃, and 195-205℃, respectively.
10. The application of an antistatic packaging composite film according to any one of claims 1-3, characterized in that, The antistatic packaging composite film is used to manufacture antistatic packaging bags for electronic component products.